A systematic mapping study on cloud-based mobile application testing - Badamasi, Imam Ya'au; Salleh, Norsaremah; Nordin, Azlin; Alwan, Ali Amer; Idris, Norbik Bashah; Abas, Hafiza (Universiti Utara Malaysia, 2019)
Mobile applications and devices have played a significant role in boosting global businesses that encompass various domains such as health, education, banking, and transportation. These tools have become indispensable for everyday activities, and its applications have been developing rapidly with diverse features and platforms. However, this has created new problems and security challenges. To ensure the quality and security of these applications, a rigorous and systematic testing using cloud-based environment is required. By employing systematic mapping study (SMS) method, this paper will examine the empirical studies that address the issues on cloud-based mobile application testing. This paper presents a total of 23 primary studies that investigate cloud based mobile application testing and the effect of Testing as a Service (TaaS). The majority of these studies (56.5%) contribute to literature with a number of framework proposals. A large proportion of the studies (60.9%) analyzed Android applications, and usually supported a single type of mobile app testing. Other than that, the majority of the studies (52.2%) have failed to investigate the outcomes of TaaS, despite a plethora of services that offers TaaS. The SMS method conducted in this paper has identified gaps in literature, which are: 1) there is a lack of general and scalable approaches to support the diverse types of mobile app testing for applications using various platforms, and 2) the lack of evaluation methods such as case study to validate the proposed approaches.